Mastering Cassandra essentials a developer's guide to horizontally scalable NoSQL database - Berglund, Tim (O'Reilly, 2017)
"Apache Cassandra is an open-source NoSQL database that specializes in speed, scale, and uptime. With technical features based on Dynamo and Google BigTable, Cassandra is one of the most widely used distributed data storage systems available. If you've got more data than can fit on one server, uptime is important to you, and if you're working with data that changes rapidly, then Cassandra is a database to think about. This tutorial provides a complete introduction to Cassandra. Not only will you understand how Cassandra distinguishes itself from relational databases and other NoSQL stores, you'll learn enough of the Java API to get started writing code. The course explores Cassandra's unique tabular data model; digs into the internal performance of each node in a Cassandra database--the read and write path; explains the operational responsibilities for maintaining a Cassandra cluster; and guides you through writing Java code that writes to and reads from a Cassandra database. If you're a developer or architect just getting started with Cassandra, or someone considering using a non-relational data store, this video tutorial will illuminate the capabilities of this massively popular NoSQL database."--Resource description page
Title from title screen (viewed November 1, 2017). - Date of publication from resource description page
Keywords: Apache Cassandra; Non-relational databases; Database management; Open source software; Bases de données non relationnelles; Bases de données; Gestion; Logiciels libres